USING THE FRACTAL DIMENSION OF EARTHQUAKE DISTRIBUTIONS AND THE SLOPE OF THE RECURRENCE CURVE TO FORECAST EARTHQUAKES IN COLOMBIA - Caneva, Alexander; Smirnov, Vladimir (Earth Sciences Research Journal, 2004)
An estimation and analysis of temporal and spatial variations (on the surface, and depending on depth) of the parameters of the seismic regime (fractal dimension of the earthquakes distribution d and slope of the seismic recurrence curve b) in Colombia are carried out, considering the fractal properties of seismicity. The variations of thedifference (b - d/a), in time are analyzed (where a is the exponent of the power law E ~ la which establishes the relation between the energy E of the earthquake and the size l of its focus). This difference describes the deviation of the geophysical medium from a "stable" state for intervals of time in which strong earthquakes occur. The possibilities to use the variations of the parameters of seismic regime to forecast earthquakes are discussed.